Five subtypes of type A gamma-aminobutyric acid receptors identified in neurons by double and triple immunofluorescence staining with subunit-specific antibodies. - Fritschy, J M (1992)
The extraordinary structural diversity of subunits forming type A gamma-aminobutyric acid (GABAA) receptors in the brain is expected to give rise to different modes of GABAergic synaptic inhibition and different profiles of modulatory drugs effective in anxiolytic, hypnotic, and antiepileptic therapy. To identify receptor subtypes in situ, the most prevalent subunits were visualized by double and triple immunofluorescence staining in rat brain, using polyclonal antibodies to the alpha 1, alpha 3, and gamma 2 subunits and a monoclonal antibody to locate both the beta 2 and the beta 3 subunit. At both cellular and subcellular levels five distinct patterns of subunit colocalization were identified: I, alpha 1 beta 2,3 gamma 2; II, alpha 3 beta 2,3 gamma 2; III, alpha 1 alpha 3 beta 2,3 gamma 2; IV, alpha 3 gamma 2; and V, alpha 1 alpha 3 gamma 2. As analyzed by confocal laser microscopy, different subunits displayed the same local variations of staining intensity ("hot spots") along the plasma membrane. The covisualized subunits appear therefore to be coassembled in receptor subtypes. Most neurons expressed only a single major receptor subtype with no apparent distinction between synaptic and extrasynaptic sites. However, in some neurons, most notably in Purkinje cells, the subunit composition varied between the soma and the dendrites, pointing to the existence of receptor heterogeneity within single neurons. Furthermore, different populations of neurons may be characterized by particular receptor subtypes. Cells displaying alpha 1-subunit immunoreactivity were mostly identified as GABAergic, whereas monoaminergic neurons displayed intense alpha 3-subunit immunoreactivity but virtually no alpha 1-subunit immunoreactivity. The allocation of defined GABAA receptor subtypes to identified neurons opens the way for a functional analysis of receptor heterogeneity.